2010
DOI: 10.4028/www.scientific.net/msf.645-648.787
|View full text |Cite
|
Sign up to set email alerts
|

4H-SiC Surface Morphology Etched Using ClF<sub>3</sub> Gas

Abstract: The morphology of a single-crystalline 4H-silicon carbide (SiC) substrate surface after etching by chlorine trifluoride (ClF3) gas was studied over the wide temperature range of 673-1573 K at atmospheric pressure in a horizontal cold wall reactor. The Si-face and C-face showed pitted surfaces at low temperatures; the pits tended to become small and shallow with the increasing substrate temperature. The etching for 0.5 min at the substrate temperature of 1573K and at the ClF3 gas concentration of 1% could maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…10 For practically applying such a high rate etching technique for electronic device fabrication, the silicon carbide surface after the etching should be carefully studied. Previous studies [3][4][5][6][7][8][9] have reported that the silicon carbide surface often had a carbon film residue after the chlorine trifluoride etching. In order to obtain a silicon carbide surface without any residue, the mechanism of carbon film formation should be clarified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 For practically applying such a high rate etching technique for electronic device fabrication, the silicon carbide surface after the etching should be carefully studied. Previous studies [3][4][5][6][7][8][9] have reported that the silicon carbide surface often had a carbon film residue after the chlorine trifluoride etching. In order to obtain a silicon carbide surface without any residue, the mechanism of carbon film formation should be clarified.…”
mentioning
confidence: 99%
“…For achieving the quick process, chlorine trifluoride (ClF 3 ) gas is a candidate, because it can etch the single crystalline 4H-silicon carbide at the high rate of several μm/min. [3][4][5][6][7][8][9] Additionally, the chlorine trifluoride gas could etch a large-diameter wafer using a large scale etcher. 10 For practically applying such a high rate etching technique for electronic device fabrication, the silicon carbide surface after the etching should be carefully studied.…”
mentioning
confidence: 99%
“…2 However, the cleaning of the silicon carbide CVD reactor has been widely recognized to be difficult, because the silicon carbide material is quite stable to chemical reactions, 3 even under severe conditions. In order to design the silicon carbide reactor cleaning process, the chemical reaction induced by chlorine trifluoride gas [4][5][6][7][8][9][10][11][12][13] is expected to be used, because chlorine trifluoride gas can quickly etch off singlecrystalline and polycrystalline silicon carbide at temperatures significantly lower than that for the film deposition. However, the carbon susceptor surface, covered with a silicon carbide coating film, may be significantly etched off by the chlorine trifluoride gas.…”
mentioning
confidence: 99%
“…For this purpose, the challenging point is the way to reduce the damage to the susceptor surface to less than an allowable level. [5][6][7] The authors have studied the chemical reactions of silicon carbide with chlorine trifluoride gas [9][10][11][12][13][14][15] in order to find the possible conditions for the in situ cleaning. [5][6][7] In these studies, two kinds of depositions, such as the particle-type and film-type, could be removed by the chlorine trifluoride gas at temperatures lower than 330 • C for a long period, such as one-two hours, with an allowable damage to the susceptor coating film.…”
mentioning
confidence: 99%